2012
DOI: 10.1186/1471-2334-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Mass drug administration significantly reduces infection of Schistosoma mansoni and hookworm in school children in the national control program in Sierra Leone

Abstract: BackgroundThe first-ever round of school-based mass drug administration (MDA) with praziquantel together with mebendazole targeting school-aged children in endemic districts was conducted in 2009 by the National Neglected Tropical Diseases Control Program. To evaluate the impact of the treatment regimen, a cross-sectional sentinel site survey was conducted 6 months post-MDA.MethodsFifteen sentinel schools from six highly endemic districts (according to data from national and pre-MDA surveys) with Schistosoma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 24 publications
3
40
2
Order By: Relevance
“…Studies have shown that MDA significantly reduces Schistosomiasis infection [31], [32]. Evidence has shown that, following chemotherapeutic cure of S. mansoni or S. haematobium infection, older individuals display a resistance to re-infection in comparison to younger children [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MDA significantly reduces Schistosomiasis infection [31], [32]. Evidence has shown that, following chemotherapeutic cure of S. mansoni or S. haematobium infection, older individuals display a resistance to re-infection in comparison to younger children [33].…”
Section: Discussionmentioning
confidence: 99%
“…Providing food for children prior to MDA, as well as treatment to alleviate and manage the side-effects attributable to praziquantel treatment, could be considered. High coverage and better compliance to treatment for schistosomiasis among school children was achieved by the national control programme in Sierra Leone when a special feeding programme for the children and supplies such as antihistamines and paracetamol to mitigate the side-effects were provided (Hodges et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers confessed that they withheld the drugs from such children because they feared they would cause serious side-effects if the children swallowed them on empty stomachs. In Swaziland, the mass treatment exercise by the national schistosomiasis control programme was suspended following hospitalization of over 800 pupils after receiving praziquantel treatment (Hodges et al, 2012). In Tanzania, treatment for schistosomiasis in schools was suspended following riots in 2008 after parents became convinced that the tablets had been sent to poison their children ).…”
Section: Discussionmentioning
confidence: 99%
“…MDA is the control strategy of choice in other parasitic diseases, such as lymphatic filariasis, schistosomiasis, and onchocerciasis [5-7]. However, current studies of MDA for malaria have shown mixed results, with some evidence of success yet no long lasting effects in either sub-Saharan Africa or the Asia Pacific [8-12].…”
Section: Introductionmentioning
confidence: 99%